Peer Learning Project for Teachers - D. A. Mezentceva; E. S. Dzhavlakh; O. V. Eliseeva; A. Sh. Bagautdinova (Высшее образование в России)
The paper deals with the issue of the faculty development at ITMO University by means of informal education in the context of implementation of new educational technologies in Russian institutions of higher education. The project team of the University designed and implemented a peer learning project which enables educators to share their experiences with technology and train each other to use new tools, methods, and techniques in their professional practice. The article describes the first results of the ITMO.EXPERT project, provides the analysis of its current state, and proposes measures for improving the efficiency of the project. The special focus in the paper is made on the analysis of such aspects of the ITMO.EXPERT project as the competencies that the participants are supposed to develop; the key characteristics of the target audience of the project that should be taken into consideration when planning improvements; the structure of a single workshop and the structure of the whole project.